‘Smiley, you’re on candid camera’: Emoticons & Pre-Digital Networks - Shep, Sydney (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherche et d’étude sur le livre au Québec, 2010)
Emoticons are usually associated with the digital age, but they have numerous precursors in both manuscript and print. This article examines the circulation of emotional icons in nineteenth-century typographical journals as a springboard to understanding the relationship between emotion, materiality, and anthropomorphism as well the pre-digital networks of the “typographical press system.” It draws on literature from textual and typographical analysis, including the history of punctuation. It also demonstrates the ubiquity of emoticons in contemporary society and culture outside the world of computers, text messaging, and chat rooms.